Reproductive Biology of the Smooth Dogfish, Mustelus canis, in the Northwest Atlantic Ocean - Conrath, Christina L.; Musick, John A. (Environmental biology of fishes, 2002)
Shark populations tend to be highly vulnerable to overexploitation due to low fecundity and slow growth rates. Recent fishing pressure on the smooth dogfish in the northwest Atlantic has created a necessity for more information about their basic biology. Length and age at maturity, fecundity, and reproductive season were estimated. Total length at 50% maturity was 102cm for females, and 86cm for males. The majority of females were mature at age 4 or 5, and all males were mature at 2 or 3 years of age. Females had an 11-12 month gestation with parturition occurring in May, ovulation occurring between May and July likely in late May and early June, and mating occurring between May and September. Fecundity ranged between 3 and 18 pups per litter, and was positively related to length and age, with a mean of 9.53 pups per litter. Sperm was found in the terminal zone of the oviducal gland of females throughout the year.[PUBLICATION ABSTRACT]